Energy – Released in Nuclear Reactions - Sultankhodjaeva Gulnoza Shukhratovna (Genius Publishing Group, 2022)
Modern civilization of unthinkable without electrical energy. Use nuclear fuel for electricity generation – an extremely tempting idea. The energy released in nuclear reactions is millions of times higher than that given by ordinary chemical reactions (for example, the combustion reaction).
Keywords: nuclear power; nuclear fuel; power deficiency; construction